2015
DOI: 10.1177/0731121415587115
|View full text |Cite
|
Sign up to set email alerts
|

“Success Is Relative”

Abstract: Previous studies have pursued whether there is an inverse relationship between levels of achievement and students' perceptions of their success. We find that these academic paradoxes exist but that they need to be analyzed in a manner that does not look only at structure or culture and that remaps what falls under both of these categories. Comparing in-depth interview data of middle-class Korean American and Mexican American college students who have realized a similar outcome, enrollment in a higher tier Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…However, these concepts can just as easily be seen as components that facilitate success if it is defined as achieving a particular goal. Furthermore, there can be a stark difference in how faculty and students define success (Dean, 1998;Thompson and Jensen-Ryan, 2018), as well as how minoritized students (which we use here to include BIPOC, first-generation, low-socioeconomic status, or other underrepresented groups of students) and their majority counterparts define the term (Tierney, 1992;Goyette and Xie, 1999;Oh and Kim, 2016;O'Shea and Delahunty, 2018). For example, in a study at a public California university, Oh and Kim (2016) found that Korean-American undergraduate students most often defined success as reaching the highest levels of academic achievement, while Mexican-American students most often defined success as going to a 4-year university, surpassing the success of their parents, and helping future students find success (Oh and Kim, 2016).…”
Section: What Is Success?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, these concepts can just as easily be seen as components that facilitate success if it is defined as achieving a particular goal. Furthermore, there can be a stark difference in how faculty and students define success (Dean, 1998;Thompson and Jensen-Ryan, 2018), as well as how minoritized students (which we use here to include BIPOC, first-generation, low-socioeconomic status, or other underrepresented groups of students) and their majority counterparts define the term (Tierney, 1992;Goyette and Xie, 1999;Oh and Kim, 2016;O'Shea and Delahunty, 2018). For example, in a study at a public California university, Oh and Kim (2016) found that Korean-American undergraduate students most often defined success as reaching the highest levels of academic achievement, while Mexican-American students most often defined success as going to a 4-year university, surpassing the success of their parents, and helping future students find success (Oh and Kim, 2016).…”
Section: What Is Success?mentioning
confidence: 99%
“…First, we suggest that universities have a policy to incorporate nonacademic measures of success into components of course work or within graduate student evaluations. Many studies have revealed that student mental health and persistence, among other outcomes, are highly impacted by nonacademic factors (i.e., not related to course or grade outcomes) such as creation of a professional network (Sweitzer, 2009), development of metacognitive regulatory strategies (Green and Macauley, 2007;Efklides et al, 2018;O'Shea and Delahunty, 2018), and establishment of students' academic identities (McAlpine and Amundsen, 2009;Oh and Kim, 2016;Schnoes et al, 2018). Depending on students' definitions of success, these factors may be as important, if not more important, than traditionally evaluated outcomes, like GPA, exam scores, or time to degree.…”
Section: Students' Rights To Have Their Views Given Due Weight-recommmentioning
confidence: 99%
“…Other researchers examine academic success in relation to the length of study from matriculation to graduation (Gilmore, Wofford, & Maher, 2016, Matheka, Jansen, & Hofman, 2020. Other researchers have analyzed and highlighted academic success by analyzing factors that influence it, such as cultural norms and family expectations (Oh & Kim, 2016). Other authors believe that a number of personal factors underlie success such as: clear goal setting and intrinsic motivation (Locke, E. A., & Latham, G. P. 2002), effective planning and time management (Covey, S. R. (1989, Allen, D. (2001, effective learning (Brown, P. C., Roediger III, H. L., & McDaniel, M. A., 2014), certain types of social behaviors such as communication and collaboration influence success, adaptability and resilience (Duckworth, A., 2016, Anghel et.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A quantitative methodology to measure the success of an intervention programme that was aimed to promote student receptivity to individuals who were either culturally or ethnically different from themselves (Oh et al, 2016). This was done in the context of the scientific tradition.…”
Section: The Ramifications Of Taking a Positivist And Logical Stancementioning
confidence: 99%